2021
DOI: 10.3390/ijms22126336
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Metastatic Heterogeneity of Tumor Marker Expression and Microenvironment Architecture in a Preclinical Cancer Model

Abstract: Background: Preclinical drug development studies rarely consider the impact of a candidate drug on established metastatic disease. This may explain why agents that are successful in subcutaneous and even orthotopic preclinical models often fail to demonstrate efficacy in clinical trials. It is reasonable to anticipate that sites of metastasis will be phenotypically unique, as each tumor will have evolved heterogeneously with respect to gene expression as well as the associated phenotypic outcome of that expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…To measure the distribution of DiR labelled liposomes in organs, the lung, liver, kidney, adrenal glands, ovaries and brain were harvested from each animal (n = 6) and imaged ex vivo or prepared for LSC of [3H]–CHE (see Methods). The selection of organs examined was based on previous studies which showed that tumors consistently developed in these sites following intracardiac injection of JIMT-1 cells [ 1 ]. The AUC 0–48 h was calculated for each organ collected from animals injected with the [3H]–CHE/DiR labelled liposomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To measure the distribution of DiR labelled liposomes in organs, the lung, liver, kidney, adrenal glands, ovaries and brain were harvested from each animal (n = 6) and imaged ex vivo or prepared for LSC of [3H]–CHE (see Methods). The selection of organs examined was based on previous studies which showed that tumors consistently developed in these sites following intracardiac injection of JIMT-1 cells [ 1 ]. The AUC 0–48 h was calculated for each organ collected from animals injected with the [3H]–CHE/DiR labelled liposomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…JIMT-1 mkate cells were injected into the left ventricle of animals to seed tumors systemically. Animals were subsequently imaged twice weekly using IVFI to assess tumor development throughout the body (see Methods and reference 1; [ 1 ]). Similar to previous studies, mice consistently developed JIMT-1 mkate tumors in the lung (6 animals), liver (6), kidney (3), ovary (6), adrenal gland (6) and brain (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the microimaging system can visualize the tissue response in a 2D manner, it integrates the fluorescence signals accumulated over the penetration depth of around 300 µm, and thus lacks three-dimensional (3D) imaging capabilities that are critical to the understanding of the drug-tissue interactions. Studies have shown that uneven drug exposure may significantly contribute to the resistance of cancers to chemotherapy [ 6 , 7 , 8 , 9 ]. Measurement of the drug penetration, distribution, and efficacy relies on advanced 3D microscopy techniques.…”
Section: Introductionmentioning
confidence: 99%